Analisis Pemahaman dan Pelanggaran Early Warning System (EWS) terhadap Angka Kecelakaan di Perlintasan Sebidang dengan Metode Chi-Square - Iswanto, Ary Putra; Imron, Nanda Ahda; Priyanto, Sapto (Politeknik Perkeretaapian Indonesia Madiun, 2021)
The research aims to determine the understanding of EWS and the number of violations with the number of accidents in the crossing of a field that occurred at the crossing of KM 287 + 8.This type of research is a case study that is research on pre-defined subjects and objects. The number of respondents examined in this study was 360 respondents, observations were conducted against the number of violations and the number of accidents carried out during 20 days of observation and understanding of respondents, while the method of analysis used was correlational method using cross tabulation (crosstab) and pearson chisqure. The results show that understanding EWS has a very weak relationship and is in line with the accident rate at the level crossing, this shows that the higher the level of understanding of a motorist's EWS, it will be able to suppress or minimize the number of accidents that occur at level crossings that have EWS and the number violations have a moderate relationship with the number of accidents at a level crossing, this shows that the higher the number of violations, the more the number of accidents that occur.